VISUALISASI PERILAKU PENGENDARA SEPEDA MOTOR SEBAGAI BENTUK CRIME IN EVERYDAY LIFE ANALISIS CULTURAL CRIMINOLOGY - Neri Widya Ramailis (UIR PRESS, 2016)
The phenomenon of traffic violations made by motorcyclists on the road is a pattern of behavior that is accustomed habit, done repeatedly and happen everyday, so as to for man aberrant culture. Then, in another case of traffic violation phenomenon is also seen as a condition of demoralization, which is interpreted as a form of the decrease to values, morality and norms in society. Where, in this case the people familiar with the rules and laws that apply, however, the rules are not well practiced in everyday life. This thesis tries to explain how cultural criminology see motorcyclists behavioral phenomena in everyday life dimension in crime and crime as culture. The method used in this research is a visual analyst criminology developed by Cecil E. Greek to display an image/photo related traffic offenses committed motorcyclists. The conclusion of this thesis is the behavior of motorcyclists present in this case as a form of crime phenomena in everyday life (crime in everyday life), and the phenomenon of crime and culture (culture as crime).